Syntactic structure and rhetorical combinations of Iranian English research article titles in medicine and applied linguistics: A cross-disciplinary study - Moslehi, Shadab; Kafipour, Reza (Frontiers in Education, 2022)
This corpus-based cross-disciplinary study investigated the syntactic structures and rhetorical combinations of 200 Research Articles titles in two disciplines, namely Medicine (100) and Applied Linguistics (100). The RA titles were selected from four reputable Iranian English journals. The authors were all Iranian researchers in these two disciplines. The titles were analyzed in light of Dietz’s (1995) taxonomy. First, the frequencies and percentages of each syntactic and rhetorical construction occurrence have been counted. Next, the authors ran a T-test regarding title length and the Chi-Square test to decide whether syntactic or rhetorical construction is a discipline-specific convention. Findings revealed that medical titles were longer than the linguistic ones. The frequency and percentage of both single- and multiple-unit RA titles were exceptionally the same in both disciplines. Concerning the syntactic components of RA single-unit titles, the most frequently used structure was the nominal construction followed by verbal and prepositional ones. The most recurrent syntactic components of nominal structure in both disciplines were post- and pre-modified, with medical titles overtaking the linguistic titles in all nominal categories. In terms of verbal constructions, the dominant structure in Medicine was full-sentence, and in Applied Linguistics, gerund phrases.